History of research performance measurement systems in the Australian higher education sector. (February 2019) - Martin-Sardesai, Ann; Guthrie, James; Tooley, Stuart; Chaplin, Sally
Performance measurement systems (PMSs) are a global phenomenon emanating from new public management (NPM) reforms. While they are now prolific and entrenched, they have attracted criticism based on their design and the manner in which they are applied. The purpose of this article is to explore the history of accounting for research in the Australian higher education sector (HES). It focuses on how successive Australian governments have steered research within the sector through the introduction of PMSs, in line with NPM reforms. Relying on publicly available online policy documents and scholarly literature, the study traces the development of performance measures within the Australian HES from the mid-1980s to 2015. It contributes to literature in management accounting aspects of NPM through the means of management accounting techniques such as PMSs. It also contributes to accounting history literature through an examination of three decades of accounting for research in the Australian HES.